(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article examines the current state, problems and prospects of the development of the bank card market in the Republic of Kazakhstan. The most pressing problems and possible prospects for the development of the bank card market are determined. Now there are positive trends in the use of bank cards, however, there are also problems, including cultural ones. Methods of statistical analysis and comparison were used in the research process.